1988
DOI: 10.1002/ddr.430140103
|View full text |Cite
|
Sign up to set email alerts
|

Lipids are major components of human immunodeficiency virus (HIV): Modification of HIV lipid composition, membrane organization, and protein conformation by AL‐721®

Abstract: The lipid composition of human immunodeficiency virus (HIV) was investigated. Several strains of HIV were found to contain considerable amounts of lipid. The major lipid constituents were cholesterol and phospholipid with a molar ratio close to one. This lipid composition and membrane apparent microviscosity, as determined by diphenylhexatriene fluorescent polarization, indicate that the HIV envelope is an extremely rigid membrane. A previous in vitro study and two recent clinical reports have indicated that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 77 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…At this time the significance of the differences in phospholipid classes between HIV-1 and HIV-2-L isolates is unknown, since the range of values of all phospholipids is within those previously reported (5,6,9,10). However, the evidence presented here lends support to the critical nature of the lipid composition of the HIV envelope derived during emergence by means of a sequestration of specific lipids from the host cell surface membrane lipid repertoire.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…At this time the significance of the differences in phospholipid classes between HIV-1 and HIV-2-L isolates is unknown, since the range of values of all phospholipids is within those previously reported (5,6,9,10). However, the evidence presented here lends support to the critical nature of the lipid composition of the HIV envelope derived during emergence by means of a sequestration of specific lipids from the host cell surface membrane lipid repertoire.…”
supporting
confidence: 61%
“…The demonstration of high levels of phospholipids normally found in cell surface membranes [sphingomyelin (Sph), phosphatidylethanolamine (PE), phosphatidylcholine (PC), and phosphatidylserine (PS)] supported the electron microscopic observations depicting the enclosure of the viral capsid with a lipid envelope derived from the host cell plasma membrane during the budding process (4,5). Further, these studies (4,5) and others (6) indicated that HIV had a low lipid-to-protein (weight) ratio and a high cholesterol-to-phospholipid molar ratio (C/P ratio).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Cholesterol was selected as the anchor since it -is highly hydrophobic and membranes of HIV and'HIVinfected cells are rich in this steroid (18).…”
mentioning
confidence: 99%